An annotated checklist of the birds of Tanjung Puting National Park, Central Kalimantan - Part 1 - Nash, Stephen V; Nash, Anne D (KUKILA, 1988)
Tanjung Puting National Park is located near the south-western corner of the island of Borneo, in Central Kalimantan province at 112 deg E, 3 deg S, and covers an area of 296,800 hectares. The park contains the largest and best representation of south western Borneo's original coastal plain habitats, particularly the predominant heath and peat swamp forests, which occupy a much larger extent here than in any other protected area in Borneo.